Profil Sikap Mencari Bantuan Layanan Psikologis pada Mahasiswa - Nurfadilah, Nurfadilah; Rahmadani, Anisa; Ulum, Bahrul (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2021)
The results of a survey by the Indonesian Psychology Student Association (ILMPI) show that students still do not understand the meaning of mental health services. Meanwhile, the results of the 2018 Basic Health Research stated that handling mental health is as important as physical health. Therefore, it is necessary to conduct research to get a picture of the attitudes of students in seeking psychological assistance in colleges. This mixed methods research was conducted at the University of Al Azhar Indonesia (UAI). Quantitative data was collected using a questionnaire on the attitude of seeking professional psychological assistance to 180 students, while the qualitative data were obtained using semi-open interviews with 12 students via telephone. The results showed that the students’ attitudes tended to be neutral in seeking psychological help; students are even less familiar with the existence of psychological services and have a negative stigma against psychological services, and the psychological service campaign that has been carried out is ineffective. In order to create students who are healthy physically and mentally, therefore, this article suggests some points. First, as mandated by Law of the Republic of Indonesia Number 18 of 2014 concerning Mental Health, derivative regulations must be made at the level of ministerial regulation which mandates that universities should develop a strategy for the implementation of sustainable, implementative, comprehensive, and integrated youth psychological service units in universities. Second, Commission X DPR RI should oversee the process of forming these derivative regulations and supervise their implementation. AbstrakHasil survei Ikatan Lembaga Mahasiswa Psikologi Indonesia (ILMPI) menunjukkan bahwa mayoritas mahasiswa masih tidak memahami maksud dari layanan kesehatan mental. Sementara hasil Riset Kesehatan Dasar tahun 2018 menyatakan bahwa penanganan kesehatan mental sama pentingnya dengan kesehatan fisik. Oleh karena itu, perlu dilakukan penelitian untuk mendapatkan gambaran tentang sikap mahasiswa dalam mencari bantuan psikologis pada perguruan tinggi. Penelitian mixed method ini dilakukan di Universitas Al Azhar Indonesia (UAI). Pengumpulan data kuantitatif dilakukan dengan menggunakan kuesioner Attitude Toward Seeking Professional Psychological Help terhadap 180 orang mahasiswa, sedangkan data kualitatif diperoleh menggunakan wawancara dengan format semi terbuka terhadap 12 orang mahasiswa via telepon. Hasil penelitian menunjukkan bahwa sikap mahasiswa cenderung netral dalam mencari bantuan psikologis; mahasiswa bahkan kurang familiar dengan keberadaan layanan psikologis, dan memiliki stigma negatif terhadap layanan psikologis; dan belum efektifnya kampanye layanan psikologis yang telah dilakukan. Demi tercapainya mahasiswa yang sehat fisik dan mental maka artikel ini menyarankan beberapa hal. Pertama, amanat Undang-Undang Republik Indonesia Nomor 18 tahun 2014 tentang Kesehatan Jiwa harus dibuatkan peraturan turunan pada tingkat penyelenggaraan universitas melalui peraturan menteri yang menangani pendidikan tinggi, yang di dalamnya mengamanatkan agar universitas menyusun strategi penyelenggaraan unit layanan psikologis remaja yang berkesinambungan, implementatif, komprehensif, dan terintegrasi dengan sumber-sumber dukungan yang dimiliki oleh perguruan tinggi. Kedua, Komisi X DPR RI sebaiknya mengawal proses pembentukan aturan turunan tersebut dan mengawasi pelaksanaannya.